The enhancing effect of a laser photochemotherapy with cisplatin or zolendronic acid in primary human osteoblasts and osteosarcoma cells in vitro. (28th April 2016) - Heymann, Paul Günther Baptist; Ziebart, Thomas; Kämmerer, Peer Wolfgang; Mandic, Robert; Saydali, Akram; Braun, Andreas; Neff, Andreas; Draenert, Guy Florian
Abstract : Background: Photodynamic therapies (PDT) have become increasingly popular in the adjuvant treatment of different tumour entities. Chemotherapeutic agents, such as cisplatin may be used in combination with low‐level laser therapy (LLLT) as laser photochemotherapy. The aim of this study was to investigate the effect of LLLT on cell bioviability of normal and malignant bone cells under chemotherapeutic conditions with either cisplatin or zolendronic acid in vitro . Methods: Primary human osteoblasts (HOB) and an osteosarcoma cell line (Saos‐2) were treated with different concentrations of zolendronic acid or cisplatin and irradiated twice with a diode laser (wavelength 670 nm, 120 s, energy outputs of 100mW/cm 2, continuous wave mode). Cell viability was tested by XTT‐assay and via histomorphological analysis. Results: LLLT alone increased bioviability for both cell lines. LLLT lowered HOB viability at the three highest concentrations of cisplatin and zolendronic acid. For Saos‐2, LLLT reduced cell viability at every concentration of cisplatin. In cases of incubation with zolendronic acid, similar to osteoblasts, LLLT lowered cell viability at the highest concentration only. Conclusions: Based on the conditions of this study, laser photochemotherapy may be able to raise the cytotoxicity of cisplatin and zolendronic acid in benign and malignant bone cells. This could be of interest in the development of new therapeutic treatment modalities against neoplastic bone diseases like osteosarcoma.